2015
DOI: 10.1212/wnl.0000000000001260
|View full text |Cite
|
Sign up to set email alerts
|

Association of prone position with sudden unexpected death in epilepsy

Abstract: There is a significant association between prone position and SUDEP, which suggests that prone position is a major risk factor for SUDEP, particularly in patients aged 40 years and younger. As such, SUDEP may share mechanisms similar to sudden infant death syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(92 citation statements)
references
References 39 publications
2
87
0
3
Order By: Relevance
“…12 We did not find any rare variants (classified as variants with a minor allele frequency of <0.1%) in five genes potentially involved in congenital central hypoventilation syndrome (CCHS), although it is likely that additional candidate genes for respiratory dysfunction exist. 49 The underpinnings of respiratory dysfunction subsequent to terminal seizures in SUDEP are likely to be a complex interplay of genetic and nongenetic factors. 48 SUDEP patients of the MORTEMUS study represent a selected refractory group undergoing presurgical evaluation, with the added aspect that the dose of their antiepileptic drugs had been reduced by more than 50%, or completely withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…12 We did not find any rare variants (classified as variants with a minor allele frequency of <0.1%) in five genes potentially involved in congenital central hypoventilation syndrome (CCHS), although it is likely that additional candidate genes for respiratory dysfunction exist. 49 The underpinnings of respiratory dysfunction subsequent to terminal seizures in SUDEP are likely to be a complex interplay of genetic and nongenetic factors. 48 SUDEP patients of the MORTEMUS study represent a selected refractory group undergoing presurgical evaluation, with the added aspect that the dose of their antiepileptic drugs had been reduced by more than 50%, or completely withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…Prone position is associated with SUDEP. 23 The significance of finding the decedent’s face (nose/mouth) against a surface (often bedding) must be interpreted in the totality of autopsy and scene findings. Such a position is potentially threatening when the brain’s reflexive response to the environmental challenge is impaired, for example, during intoxication or during/after seizure.…”
Section: Resultsmentioning
confidence: 99%
“…Assumptions were made about SUDEP occurring during sleep if the person was found dead in bed, and during wakefulness if found outside of the bed or bedroom. 8 Of the 253/413 SUDEP cases reviewed in which body position was adequately documented, 73.3% were prone (p , 0.001). Of note, in the 11 cases that had SUDEP documented on video-EEG, 100% were found prone, had had a generalized tonic-clonic seizure, and had PGES.…”
Section: Facing Up To Sudepmentioning
confidence: 99%
“…One potential modifiable risk factor has been identified: being found in bed in the prone position; however, there were no large studies to confirm this. 8 In this issue of Neurology ® , Liebenthal et al 8 describe their systematic review and meta-analysis of the literature up to 2003 in which they found 25 studies (of 1,106 unique ones): 14 single case studies and 11 case series where body position was documented in relation to the SUDEP. These authors used the Nashef definition of SUDEP: witnessed or unwitnessed, nontraumatic and nondrowning, excluding status epilepticus or an identifiable cause of death at autopsy 9 ; cases were divided into definite (autopsy-proven), probable (no autopsy), or possible (other cause of death was listed).…”
Section: Facing Up To Sudepmentioning
confidence: 99%